Effect of Decellularized Cartilage Bovine Scaffold and Hypoxic Condition on Stem Cell Differentiation to Chondrocyte: An In Vitro Study - Ferdiansyah Mahyudin, NIDN. 8890010016 (Trans Tech Publications, Switzerland, 2018)
Autologous Chondrocyte Implantation (ACI) has been established for years to treat cartilage defect. Application of tissue engineering has advantages over ACI as tissue engineering requires simpler procedures without leaving morbidity at the donor site. Decellularized bovine cartilage scaffold and hypoxic stem cell differentiation were used in this in vitro experimental study. Comparative test was done between three study groups using bone marrow mesenchymal stem cells treated in three different conditions: growth factor-rich chondrogenic medium, scaffold without growth factor, and combination of both. Each group was given two oxygen tension conditions of normoxia and hypoxic within phase of stem cell differentiation. Immunohistochemical examinations on SOX9, RUNX2, and collagen type II were done for evaluation. After 5-week treatment, the result showed that the highest expression SOX9 and collagen type II were found within the group that used the combination of both scaffold and chondrogenic medium in hypoxic condition. Collagen type II expression in scaffold without additional growth factor showed no statistically significant difference compared with the combination group in hypoxic condition. Cartilage tissue engineering has proven its effectiveness for cartilage regeneration. Decellularized biomaterial scaffold limited the use of growth factor resulting in better cost and resource efficiency.